Advanced materials for sustainable development - Suzuki, Atsushi, 1956-; Sundararajan, G., 1953- (Advanced materials research, 2010)
The purpose of this special volume was to provide young scientists from Asian countries with the opportunity of exchanging information on scientific research. It covers recent progress, achievements and innovations made in the field of advanced materials research and technology for a sustainable future world; especially in India, Japan and other Asian countries. The selected papers include experimental studies of structure, electrical and magnetic properties, thermodynamic and electrochemical properties, absorption, luminescence, permeability and self-assembly in systems involving steel and al.